Basis Data Relasional Untuk Penyimpanan Data Bertipe Bebas Pada Aplikasi Berbasis Web - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT The rapid growth in computer network and communication technology has led too fast development and wide range of applications of Internet. Web-based applications found in Internet are now. making the user easier to access information. Such condition is the result of the use of Common Gateway Interface (CGI), which enables the user (client) not only to receive information but also to send data to the server and stored in a database located in the server. Using CGI, data or requests sent by a client can be processed by the server and the server will make a response which may be necessarily sent to the requesting client or not. This paper discusses a variation of relational database applications for managing data of various types with a fixed number of tables, so that data type restriction in a conventional application of relational database can be reduced and the flexibility of the use of the database is increasing. A number of data from various entities having quite different characteristics are taken as the :example to clarify the concept. A web application using designed database is then developed to test the working of the concept. The relational database used here includes some tables whose data are mostly of character or text type. One of the tables is used to store the coding of entities' attributes. It can be seen that the structure of the database is stable, in the sense that the structure needs not be changed though the data being input come from various entities with various attributes and of various types. Furthermore, this structure is possibly developed and extended to other fields. Using the structure, data exchange will not lead to misinterpretation if the agreement on attribute coding is already achieved.